2003
DOI: 10.1046/j.1492-7535.2003.00052.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive In‐Center Hemodialysis for Children: A Case for Longer Dialysis Duration

Abstract: In this pediatric cohort, intensive center hemodialysis was associated with excellent growth, nutrition, Ca, P, and anemia control and reasonable blood pressure values. Large multicenter studies are needed to better determine optimal dialysis therapy for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…Nevertheless only a part of them will exhibit significant catch-up growth [1,2,4,5]. A first case reported as "anecdotal experience" [12], and the well known impact of enhancing both nutrition and clearance on growth velocity [8][9][10], prompted us to analyze the impact of intensified and daily on-line hemodiafiltration on growth velocity used as a sensitive dialysis adequacy parameter. The present study included only five children, but five consecutively referred patients with a long medical history.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless only a part of them will exhibit significant catch-up growth [1,2,4,5]. A first case reported as "anecdotal experience" [12], and the well known impact of enhancing both nutrition and clearance on growth velocity [8][9][10], prompted us to analyze the impact of intensified and daily on-line hemodiafiltration on growth velocity used as a sensitive dialysis adequacy parameter. The present study included only five children, but five consecutively referred patients with a long medical history.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, despite a better comprehension of the different factors implicated in the growth retardation, the statural growth velocity, even under growth hormone (rhGH) supplementation, remains often quite poor in children undergoing long term chronic hemodialysis [1][2][3][4][5][6][7]. Therefore, an enhanced uremic toxins blood purification was proposed [8], combining an increase in dialysis dose [9], and/or longer dialysis duration [10]. But so far, no conclusive results on growth have been made available [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple factors (e.g., nutritional, metabolic, and endocrine abnormalities) are identified in the pathophysiology of growth failure within the pediatric uremic syndrome. Although unexplored yet, it is very likely that uremic toxins directly affect growth since several studies demonstrated that enhanced removal, by applying intensified and daily hemodialysis, improved growth velocity compared to conventional hemodialysis [9,[15][16][17][18]. Although these studies were observational and uncontrolled, the catch-up growth achieved in these populations is striking, as standard treatment with adequate nutrition in children on maintenance hemodialysis remains associated with a mean loss in height SDS of − 0.4 to − 0.8 [19].…”
mentioning
confidence: 99%
“…Therefore, clinical outcome studies in the pediatric uremic syndrome almost inevitably depend on consideration of other patient relevant outcomes, which may be both short term, e.g., growth, pubertal development, bone metabolism, cardiovascular risk factors, and schooling, as well as long term such as premature cardiovascular disease. Additionally, school absenteeism, education level, and parental stress and burnout are important and unique endpoints in the pediatric uremic syndrome [16]. Several of these parameters are patient-centered and relevant to social life (growth, pubertal development, school absenteeism, familial stress), which will allow to highlight novel and up to now often neglected aspects of uremia.…”
mentioning
confidence: 99%